Advancing the Development of Glycated Protein Biosensing Technology: Next-Generation Sensing Molecules - Kameya, Miho (J Diabetes Sci Technol, 2015)
Research advances in biochemical molecules have led to the development of convenient and reproducible biosensing molecules for glycated proteins, such as those based on the enzymes fructosyl amino acid oxidase (FAOX) or fructosyl peptide oxidase (FPOX). Recently, more attractive biosensing molecules with potential applications in next-generation biosensing of glycated proteins have been aggressively reported. We review 2 such molecules, fructosamine 6-kinase (FN6K) and fructosyl amino acid-binding protein, as well as their recent applications in the development of glycated protein biosensing systems. Research on FN6K and fructosyl amino acid-binding protein has been opening up new possibilities for the development of highly sensitive and proteolytic-digestion-free biosensing systems for glycated proteins.